An Analysis of Factors Affecting Indonesia's Foreign Exchange Reserve - Suripto Suripto; Rai Rake Setiawan; Istanti Istanti; Hamim Mustofa (Optimum: Jurnal Ekonomi dan Pembangunan, 2022)
Foreign exchange reserves is an economic variable that is very important to pay attention to. International trade is something that makes foreign exchange reserves important. Foreign exchange is calculated by a country as property or wealth in foreign currency. In this study, research related to factors that can affect the position of Indonesia's foreign exchange reserves will be carried out. The data used is obtained from the official website of Bank Indonesia on the publication page. The data obtained is then carried out in an empirical time series from 2010 to 2020 in the form of quarters or three months. This research uses Partial Adjustment Model analysis. The results of this study indicate that exports have a positive and significant effect in the short term and have a positive but not significant effect. Imports have a negative and significant effect in the short term, and have a negative and significant effect in the long term. then interest rates do not have a significant effect in the short term or long term. foreign debt has a positive and significant effect in the short term, but does not have a negative and insignificant effect in the long term.